Emergent interventional approach for aortogastric tube fistula with massive gastrointestinal bleeding. (6th February 2015) - Kuhara, Asako; Koganemaru, Masamichi; Onitsuka, Seiji; Abe, Toshi
Abstract : This report describes the successful endovascular treatment of a rare case of aortogastric tube fistula with massive gastrointestinal haemorrhage. The patient's history included oesophageal reconstruction for oesophageal carcinoma using a gastric tube. Emergent angiography revealed extravasation from the thoracic aorta into the thinner aortogastric tube fistula. A microcatheter was inserted into the aortogastric tube with the aortic approach for embolisation with a mixture of n -butyl cyanoacrylate and iodised oil to enable fluoroscopic visualisation. Aortography confirmed the complete absence of extravasation after embolisation, after which a stent graft was placed. This procedure demonstrated that transcatheter embolisation of the aortogastric tube fistula was possible, and that the technique can be used as an emergency option. CT imaging was performed 21 days after the procedure, and revealed no trace of extravasation or inflammation. There were no complications during the 14 months following the endovascular treatment; the patient remains in stable condition.